Invitations to Tender for Facility Management Services Process Mapping, Service Specifications and Innovative Scenarios - Talamo, Cinzia; Atta, Nazly; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book deals with Invitations to Tender (ITTs) for the provision of Facility Management (FM) services. It presents a framework to support companies in preparing clear, comprehensive and effective ITTs, focusing on such key aspects as: organizational structures, tools and procedures for managing information, allocation of information responsibilities, procedures for services monitoring and control, quality policies, and risk management. It discusses and analyzes a range of basic terms and concepts, procedures, and international standards concerning the Tendering Process, as well as the contents of ITTs, which should represent the translation of information needs into requirements related to: the client's goals, main categories of information to deal with, expected organization of information, modalities of reporting and control, and level of knowledge to be reached. A further major focus is on potential key innovation scenarios concerning current FM practice, such as Sustainable Procurement, Building Information Modeling (BIM), Big Data and Internet of Things (IoT) technologies, highlighting both the possible benefits and the possible risks and implications that could negatively affect the quality of FM service provision if not properly treated within the ITT. The book will be of interest to real estate owners, demand organizations and facility managers, enhancing their ability to prepare, interpret and/or critically analyze ITTs.
Introduction -- Tendering process and Facility Management Agreements. The role of Invitation to Tender -- "Process approach" to external FM service provision -- FM services and Organizational structures Management of FM-related Information -- FM Service Monitoring and Control -- FM Service Quality and Requirements -- Analytical framework for ITTs -- FM services Procurement and Management: scenarios of innovation -- Conclusions -- Glossary.
Keywords: Facility management; Project management; Application software; Facility Management; Project Management; Computer and Information Systems Applications